META ANALISIS: PENGEMBANGAN SOAL HOTS UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK - Weni Febrianti; Zulyusri Zulyusri; Lufri Lufri (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2021)
21st century learning requires students to have 3 important abilities including critical thinking skills, creative thinking and problem solving. This ability is known as higher order thinking skills or HOTS (Higher Order Thinking Skill). This ability is used to face the challenges of the 21st century. Critical and creative thinking is needed in solving problems. This is due to the rapid development of science and technology so that it becomes new challenges and problems that students must face in 21st century learning. Based on Indonesia's ranking in PISA and TIMSS, it is necessary to develop HOTS questions to improve students' critical thinking skills. This study aims to analyze the development of HOTS questions to improve students' critical thinking skills. This research is a type of meta-analysis research. Sources of data come from national journals for the last three years. The results showed that the development of HOTS questions was able to improve students' critical thinking skills. But not only that, it can also improve students' higher order thinking skills. This is in accordance with the findings of research which shows that the development of HOTS questions to improve students' critical thinking skills can be done at all levels, both SD, SMP and SMA with an average effect size of 1.33; 1.54; and 1.26. with the effect size category at the SMA level higher than SMP and SD. Meanwhile, analyzing HOTS questions to improve critical thinking skills obtained three abilities, namely the ability to think critically, think creatively and solve problems with consecutive categories, namely 2.22; 2.03; and 2,1. This shows that the HOTS Question is able to improve the critical thinking skills of students from various levels, both SD, SMP and SMA. However, this is very suitable for use at the high school level.